2012
DOI: 10.1007/s10463-012-0376-7
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Palm likelihood theory for stationary point processes

Abstract: In the present paper, we propose a Palm likelihood approach as a general estimating principle for stationary point processes in R d for which the density of the second-order factorial moment measure is available in closed form. Examples of such point processes include the Neyman-Scott processes and the log Gaussian Cox processes. The computations involved in determining the Palm likelihood estimator are simple. Conditions are provided under which the Palm likelihood estimator is consistent and asymptotically n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Palm likelihood inference for M 1 and M 2 was considered in Tanaka et al (2007), where the two models are called the Thomas model and generalized Thomas model of type B, respectively. Prokešová and Jensen (2010) showed that the Palm likelihood estimator for these models is consistent and asymptotically normally distributed.…”
Section: Model Selectionmentioning
confidence: 98%
“…Palm likelihood inference for M 1 and M 2 was considered in Tanaka et al (2007), where the two models are called the Thomas model and generalized Thomas model of type B, respectively. Prokešová and Jensen (2010) showed that the Palm likelihood estimator for these models is consistent and asymptotically normally distributed.…”
Section: Model Selectionmentioning
confidence: 98%
“…This approach has been widely adopted in many previous articles. Examples include Guan and Loh (2007), Guan and Shen (2010), Waagepetersen andGuan (2009), Guan, Jalilian, andWaagepetersen (2015), Prekešová and Jensen (2013), and Schoenberg (2005).…”
Section: Asymptotic Distributionmentioning
confidence: 99%
“…To prove Theorem 4.2 (a), we use the blocking technique introduced by Ibragimov and Linnik (1971) and applied to spatial point processes by Guan and Loh (2007); and Prokešová and Jensen (2013). To this end, we need additional notation.…”
Section: A2 Proof Of Proposition 41mentioning
confidence: 99%